The breeding ranges of Central European and Arctic bird species move poleward. - Brommer, Lehikoinen, Valkama (United States, 2022)
BACKGROUND\nClimatic warming predicts that species move their entire distribution poleward. Poleward movement of the 'cold' side of the distribution of species is empirically supported, but evidence of poleward movement at the 'warm' distributional side is relatively scarce.\nMETHODOLOGY/PRINCIPAL FINDING\nFinland has, as the first country in the world, completed three national atlas surveys of breeding birds, which we here use to calculate the sizes and weighted mean latitudes of the national range of 114 southern and 34 northern bird species during three periods (1974-1979; 1986-1989; 2006-2010), each denoting species presence in approximately 3 800 10 × 10 km2 squares. We find strong evidence that southern species (breeding predominantly in central Europe) showed a latitudinal shift of 1.1-1.3 km/year poleward during all three pairwise comparisons between these atlases (covering 11, 20.5 and 31.5 years respectively). We find evidence of a latitudinal shift of 0.7-0.8 km/year poleward of northern boreal and Arctic species, but this shift was not found in all study periods and may have been influenced by increased effort put into the more recent surveys. Species showed no significant correlation in changes in range size and weighted mean latitude between the first (11 year) and second (20.5 year) period covered by consecutive atlases, suggesting weak phylogenetic signal and little scope of species characteristics in explaining latitudinal avian range changes.\nCONCLUSIONS\nExtinction-driven avian range changes (at the 'warm' side) of a species' distribution occur at approximately half the rate of colonisation-driven range changes (at the 'cold' side), and its quantification therefore requires long-term monitoring data, possibly explaining why evidence for such changes is currently rare. A clear latitudinal shift in an assemblage of species may still harbour considerable temporal inconsistency in latitudinal movement on the species level. Understanding this inconsistency is important for predictive modelling of species composition in a changing world.